Impact of the institutional model on psychiatric patients in Chile from the 19th to 21st centuries: a scoping review - Vivaldi Macho, Ennio; Gomez Barbieri, Gustavo; Lechuga, Hernán; Soto-Suazo, Mauricio (Frontiers in Psychiatry, 2023)
Introduction Various mental health hospital models have been tested in Chile since its foundation. The institutional model with the Asylum and the Madhouse prevailed during the nineteenth century and much of the twentieth. But is deinstitutionalizing all psychiatric patients the solution? Evidence acquisition A PubMed, Epistemonikos, Lilacs, and Google Scholar Scoping Review was carried out in the last 5 years using the PRISMA-P method and the Scoping review search strategy. The MeSH terms (“Psychiatry/history” AND “Chile”) OR (“Mental disorders” AND “therapy”) were used during the search. Finally, papers focused on clinical trial therapy evaluation were excluded, and we emphasized the effects of historical evidence. Evidence synthesis We identified 35 primary studies, and we counted the number of articles included in the review that potentially met our inclusion criteria and noted how many studies had been missed by our search. We analyzed 10 primary studies and 10 primary historical resources that were included in this study. Conclusion The state must become a guarantor and be responsible for its psychiatric patients and provide professional and humanitarian support to its patients, be it through community psychiatry, day hospitals, devices such as mental health clinics, or psychiatric institutes dedicated to teaching and research. Patients should not be left to the free will of their direct relatives, but rather the state should strengthen the primary care system.